2001
DOI: 10.1053/jlts.2001.20786
|View full text |Cite
|
Sign up to set email alerts
|

De novo hepatitis B after liver transplantation from hepatitis B core antibody—Positive donors in an area with high prevalence of anti-HBc positivity in the donor population

Abstract: Transmission of hepatitis B virus (HBV) infection from T he acquisition of hepatitis B virus (HBV) infectionafter liver transplantation remains a significant problem in the liver transplant setting. Although de novo HBV infection may occur as a result of the reactivation of occult HBV infection in the recipient, 1,2 recent reports suggest that the vast majority of acquired HBV infections after liver transplantation are related to the donor liver. Liver grafts from donors who are hepatitis B surface antigen neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
238
3
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(254 citation statements)
references
References 14 publications
11
238
3
2
Order By: Relevance
“…32,39,40 These findings are consistent with our earlier reports of SOI continuing for life after termination of acute WHV hepatitis, 30,32,37 along with documented infectivity and liver pathogenic competence of the silently carried virus. 30,32 The current results also agree with the data from the limited studies of apparently healthy individuals reactive for anti-HBc alone or anti-HBc and anti-HBs, which showed presence of HBV cccDNA and HBV RNA in their liver 8,41 and transmission of HBV by liver grafts [15][16][17][18][19][20][21] or blood [42][43][44] to virusnaïve recipients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…32,39,40 These findings are consistent with our earlier reports of SOI continuing for life after termination of acute WHV hepatitis, 30,32,37 along with documented infectivity and liver pathogenic competence of the silently carried virus. 30,32 The current results also agree with the data from the limited studies of apparently healthy individuals reactive for anti-HBc alone or anti-HBc and anti-HBs, which showed presence of HBV cccDNA and HBV RNA in their liver 8,41 and transmission of HBV by liver grafts [15][16][17][18][19][20][21] or blood [42][43][44] to virusnaïve recipients.…”
Section: Discussionsupporting
confidence: 89%
“…This outcome was consistent with the earlier findings of anti-HBc along with HBV DNA in serum and peripheral blood mononuclear cells (PBMC) 12 and a vigorous cytotoxic T-lymphocyte response to HBV antigens in apparently completely healthy individuals years after recovery from acute hepatitis B. 13,14 Moreover, transmission of HBV from blood and organ donors with isolated anti-HBc to virus-naïve individuals 5,[15][16][17][18][19][20][21] and reactivation of the infection in anti-HBc-positive persons 22,23 have been reported. Also, it is perceived that occult HBV infection with or without anti-HBc is associated with an increased risk of developing hepatocellular carcinoma.…”
supporting
confidence: 90%
“…Several studies have reported a 16.6% to 95% increased incidence for HBV infection in these patients. [1][2][3][4][5][6][7][8][9][10][11][12] As a result, many centers do not use antiHBc-positive donors for recipients without previous HBV infection. 11 These results were derived mostly from studies performed in geographic regions with a low prevalence (3% to 5%) of anti-HBc-positive liver donors.…”
Section: E Novo Hepatitis B Virus (Hbv) After Orthotopicmentioning
confidence: 99%
“…4,5 There have been documented instances of de novo occurrence of hepatitis B (HBV) infection in recipients of these organs. 3,5,[6][7][8][9][10][11] The reported rates of de novo HBV in HBcAb-negative recipients receiving an HBcAb-positive donor liver vary from 30% [6][7][8] to up to 80% 3,9,20 when no antiviral prophylaxis is used after surgery.…”
mentioning
confidence: 99%